Optimization of novel bio-composite packaging film based on alkali-treated Hemp fiber/polyethylene/polypropylene using response surface methodology approach - Dixit S.; Mishra G.; Yadav V.L. (My University, 2025)
The objective of this research was to apply a novel approach viz. Alkali treated hemp fiber (HF) was used as a process variable for optimization of the properties of polyethylene (PE)/polypropylene (PP)-based bio-composite packaging film using central composite design-response surface methodology (CCD-RSM). The optimum conditions for three process variables, i.e., PE, PP, and alkali-treated hemp fiber, were predicted using RSM and then confirmed experimentally. The optimum results were PE (1.8 g), PP (1.118 g), and treated HF (1.2 g) provided the highest mechanical stability and lowest water vapor transmission rate (WVTR) as compared to native-hemp fiber (NHF)-based composite film. The ANOVA analysis confirmed the packaging film properties were highly dependent on treated HF followed by PE and PP, respectively, in desired composites. Thus, WVTR and mechanical strength are one of the reliable indexes to evaluate packaging properties. The film prepared using optimum independent factors were also characterized by different analytical techniques such as Thermogravimetric Analysis (TGA), contact angle, optical characteristics test, impact test, and water vapor permeability (WVP). Those findings showed Contact angle, impact strength, and transparency were increased by 30%, 24%, and 66%, respectively, whereas WVP was decreased by 57%, respectively as compared to NHF-based film. Thus, Alkali-treated hemp fiber-based bio-composite film properties were comparable with pure polymeric or real polyethylene packaging films, declaring its suitability for green applications. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.